Self-Directed Learning Readiness of the Undergraduate Nursing Students: A Study from Eastern Nepal - Koirala, Namu; Kafle, Shyam P (Birat Journal of Health Sciences, 2021)
Introduction: Self-directed learning is one of the concepts of learning which is mostly used in higher education, especially in the discipline of medicine and paramedics.Objectives: The objectives of this study were to assess the self-directed learning readiness of the undergraduate nursing students and to find out its association with selected demographic variables.Methodology: A descriptive, quantitative, cross-sectional study was undertaken among undergraduate nursing students from three nursing colleges of Eastern Nepal; from January 2019 to August 2020. The nursing colleges were randomly selected; one constituent nursing college and two colleges affiliated to Purbanchal University. Census sampling method was adopted and 565 students were enrolled. Ethical clearance was taken from the Institutional Review Committee of the institute. Data was collected using a self administered, valid and standard tool: Williamson's Self Rating Scale for Self-directed Learning (SRSSDL) via online google forms, then transferred to Microsoft EXCEL. Data analysis was done using SPSS 16.0 version. Mean, median, standard deviation, range, chi-square test, Mann Whitney U test and Kruskal Wallis H test were used for data analysis.Result: Overall Self-directed Learning score was 244.83±30.15. The majority of the respondents (79.3%) had high scores of SRSSDL (221-300) and 20.7% of the respondents had moderate levels of SRSSDL (141-220). The demographic variables didn't exert any significant effect on the overall level of SRSSDL but varied only with the sub-dimensions of SRSSDL.Conclusion: This study shows that overall self-directed learning among nursing students is moderate to high and the subdimensions have significant associations with demographics and academic level.